Solution of the problem of identification of metal heating process model at heat exchange by radiation - V. B. Kovalevski; V. I. Timoshpolski; G. Romadan; V. V. Sukhan (Литьë и металлургия, 2002)
The results of parametric identification of the mathematical model of fine elements heating by radiation in pusher furnaces of modern construction are given.